Chemical modification of ED-20 epoxy oligomer by 1,4-butanediol - Bratychak, M.M.; Ivashkiv, O.P.; Astakhova, O.T. (Reports of the National Academy of Sciences of Ukraine, 2014)
The chemical modification of ED-20 epoxy oligomer by 1,4-butanediol has been studied with the aim of synthesizing a reactive oligomer with epoxy, primary hydroxyl, and secondary hydroxy groups in its structure. The effect of the catalyst nature and amount, as well as the temperature, on the reaction rate has been determined. The effective reaction rate constants and the activation energy were calculated. The reactive oligomer based on ED-20 commercial epoxy oligomer and 1,4-butanediol has been synthesized and characterized. The possibility of its use as an additive to epoxy-oligomeric mixtures with the participation of 4,4′-diphenylmethanediisocyanate has been shown.